2023
DOI: 10.3389/fgene.2023.1105900
|View full text |Cite
|
Sign up to set email alerts
|

Pan-cancer analysis of ADAMs: A promising biomarker for prognosis and response to chemotherapy and immunotherapy

Abstract: Background: Members of a disintegrin and metalloproteinase (ADAM) family play a vital role in cancer development. However, a comprehensive analysis of the landscape of the ADAM family in pan-cancer remains to be performed.Methods: The correlation of the expression level and prognostic value with ADAMs in a pan-cancer cohort and the relationship between ADAMs and the stemness score, tumour microenvironment (TME), chemotherapy-related drug sensitivity, immune subtype, and immunotherapy outcome were investigated.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 49 publications
0
1
0
Order By: Relevance
“…ADAM23 silencing plays a key role in tumor metastasis and progression by downregulating αvβ3 integrin activation [ 45 ]. In a pan-cancer study, ADAMs were found to be differentially expressed in tumor tissues, associated with prognosis, tumor immune scores and drug sensitivity of tumors [ 46 ]. Considering its role in αvβ3 integrin activation, ADAM23 may be a potential biomarker for anti-integrin therapies in head and neck cancer, which have been a recent focus area of research [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…ADAM23 silencing plays a key role in tumor metastasis and progression by downregulating αvβ3 integrin activation [ 45 ]. In a pan-cancer study, ADAMs were found to be differentially expressed in tumor tissues, associated with prognosis, tumor immune scores and drug sensitivity of tumors [ 46 ]. Considering its role in αvβ3 integrin activation, ADAM23 may be a potential biomarker for anti-integrin therapies in head and neck cancer, which have been a recent focus area of research [ 47 ].…”
Section: Discussionmentioning
confidence: 99%